2020
DOI: 10.5964/jspp.v8i2.1178
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between collective narcissism and group-based moral exclusion: The mediating role of intergroup threat and social distance

Abstract: In our study, we investigated the relationship between collective narcissism and group-based moral exclusion. Since collective narcissists are motivated to see their group as unique and superior, and tend to show hostility towards outgroups threatening this presumed superiority, we hypothesized that perceived intergroup threat and social distance can mediate the relationship between collective narcissism and group-based moral exclusion. We tested this assumption in two intergroup contexts by investigating the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…This finding extends previous theorizing and research which showed that collective narcissism was associated with negative attitudes toward members of lower status groups within the group. For example, past research showed that national narcissism is related to prejudice towards lower status members of the national group, such as women or sexual and ethnic minorities, who might be seen as less representative of the overarching ingroup (Golec de Zavala & Bierwiaczonek, 2020;Golec de Zavala, Cichocka, & Bilewicz, 2013;Górska & Mikołajczak, 2015; see also Hadarics et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…This finding extends previous theorizing and research which showed that collective narcissism was associated with negative attitudes toward members of lower status groups within the group. For example, past research showed that national narcissism is related to prejudice towards lower status members of the national group, such as women or sexual and ethnic minorities, who might be seen as less representative of the overarching ingroup (Golec de Zavala & Bierwiaczonek, 2020;Golec de Zavala, Cichocka, & Bilewicz, 2013;Górska & Mikołajczak, 2015; see also Hadarics et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Those who are high in collective narcissism also tend to respond with hostility to any stings of criticism or lack of appreciation of the ingroup (Golec de Zavala, Cichocka, & Iskra-Golec, 2013;Gries et al, 2015) and are prejudiced towards groups they find threatening (e.g., Bertin et al, 2022;Golec de Zavala, Cichocka, & Bilewicz, 2013;Lyons et al, 2010;Marchlewska et al, 2019). Crucially, collective narcissism has been linked to perceptions of threats from immigrants (e.g., Hadarics et al, 2020;Lyons et al, 2010) and generally negative attitudes towards immigration (Marchlewska et al, 2018).…”
Section: Distinguishing Ingroup Identification From Collective Narcis...mentioning
confidence: 99%
“…with generally negative outgroup attitudes (for a review, see Golec de Zavala et al, 2019). For example, perceived intergroup threat mediated the relationship between Hungarian national narcissism and moral exclusion of Roma and Muslim immigrants (Hadarics et al, 2020).…”
Section: The Mediating Role Of Intergroup Threatmentioning
confidence: 99%
“…Of importance, defensive group beliefs displayed by national narcissists and leading to prejudice against immigrants might not only be explained by perceiving intergroup threat. Indeed, Hadarics et al (2020) suggested that "blaming outgroups may not just increase salience of in-groups but also mobilize collective action against the out-group" (p. 120). That is, for prejudice (e.g., collective action) to occur, perceived intergroup threat may take the form of blaming outgroups, encompassing sentiments that are typical of conspiracy theories.…”
Section: The Mediating Role Of Intergroup Threatmentioning
confidence: 99%